2009
DOI: 10.1186/1471-2407-9-61
|View full text |Cite
|
Sign up to set email alerts
|

Expression of Bmi-1 is a prognostic marker in bladder cancer

Abstract: BackgroundThe molecular mechanisms of the development and progression of bladder cancer are poorly understood. The objective of this study was to analyze the expression of Bmi-1 protein and its clinical significance in human bladder cancer.MethodsWe examined the expression of Bmi-1 mRNA and Bmi-1 protein by RT-PCR and Western blot, respectively in 14 paired bladder cancers and the adjacent normal tissues. The expression of Bmi-1 protein in 137 specimens of bladder cancer and 30 specimens of adjacent normal bla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
79
1

Year Published

2009
2009
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 91 publications
(87 citation statements)
references
References 34 publications
7
79
1
Order By: Relevance
“…Bmi-1 may be new diagnostic and prognostic marker in multiple different tumors including medulloblastoma (22), tongue squamous cell carcinoma (23), colon carcinoma (24), breast carcinoma (11), bladder carcinoma (25). However, precise molecular regulation mechanism of Bmi-1 in breast carcinoma remains elusive, promting the authors to investigate the possible molecular ONCOLOGY REPORTS 25: 409-418, 2011 Figure 5.…”
Section: Discussionmentioning
confidence: 99%
“…Bmi-1 may be new diagnostic and prognostic marker in multiple different tumors including medulloblastoma (22), tongue squamous cell carcinoma (23), colon carcinoma (24), breast carcinoma (11), bladder carcinoma (25). However, precise molecular regulation mechanism of Bmi-1 in breast carcinoma remains elusive, promting the authors to investigate the possible molecular ONCOLOGY REPORTS 25: 409-418, 2011 Figure 5.…”
Section: Discussionmentioning
confidence: 99%
“…11,12 In previous NSCLC studies, Vonlanthen et al 18 reported no association of Bmi1 expression with tumor characteristics (proliferation rate, differentiation, and size) or prognosis, whereas Vrzalikova et al 20 reported that Bmi1 expression was correlated with advanced stage and poor disease-free survival, but not with overall survival. For other types of cancer, some studies demonstrated that overexpression of Bmi1 was correlated with a poor prognosis [42][43][44] ; however, others reported that loss of Bmi1 expression was correlated with an aggressive phenotype, indicating a protective role of the Bmi1 protein. [45][46][47] Abundant expression of Bmi1 in normal bronchial epithelial cells in the current study and in a previous report 19 and low Bmi1 expression in the majority of tumor cells suggest that Bmi1 may have a protective role in NSCLC.…”
Section: Bmi1 and Ezh2 Expression In Nsclc/kikuchi Et Almentioning
confidence: 99%
“…The results indicate that inhibition of U937 cell proliferation by BMI-1 siRNA is mediated by upregulation of p16 which arrested the cell at G1 to S phase in its cell cycle (25,26). p16Ink4a is a downstream target of Bmi-1 (4,14), and in the absence of Bmi-1 the cyclin-dependent kinase inhibitor gene p16Ink4a is upregulated (27). Both flow cytometric apoptosis assay and TUNEL assay showed that Bmi-1 specific siRNA treatment resulted in a significant increase in the percentage of cell apoptosis.…”
Section: Discussionmentioning
confidence: 99%
“…Bmi-1 is also essential for leukemic stem cells and perhaps other type of cancer stem cells. It is overexpressed in both hematological malignancies (8)(9)(10) and solid tumors such as non-small cell lung cancer (11), liver (12), breast (13), bladder cancer (14), prostate carcinomas (15) and Ewing sarcoma (16). Therefore, BMI-1 plays an important role in regulating the proliferation of both normal and leukemia stem cells, which is useful as a novel molecular marker to predict the progression and prognosis, and may become clinically useful as a noninvasive diagnostic marker (17)(18)(19)(20)(21).…”
Section: Introductionmentioning
confidence: 99%